(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Polymer composite materials are a type of engineered composite material that combine a polymer matrix with reinforcement materials. These composites offer a range of desirable properties, including strength, durability, and lightweight characteristics. They are widely used in various industries, such as automotive, aerospace, construction, and more. Let’s explore the key aspects of polymer composite materials. The article conducts scientific research on the production of polymer-composite leathers as an alternative to chrome tanning. In particular, methods of tanned tanning (vegetable tanning agents) are being developed.